Priorities of the professoriate : engaging multiple forms of scholarship across rural and urban institutions - Bonner, Fred A.; Banda, Rosa M.; Robinson, Petra A.; Lewis, Chance W.; Lofton, Barbara (Contemporary perspectives on access, equity, and achievement., 2015)
Established in 2006, the American Association of Blacks in Higher Education (AABHE), formerly constituted as the Black Caucus (American Association of Higher Education), has been the consistent voice of Black issues in academe. According to the stated mission, the AABHE pursues the educational and professional needs of Blacks in higher education with a focus on leadership, equity, access, achievement and other vital issues impacting students, faculty, staff, and administrators. AABHE also facilitates and provides opportunities for collaborating and networking among individuals, institutions, groups and agencies in higher education in the United States and internationally. This 2012 year will mark the beginning of the AABHE research consortium, an arm of the organization that will advance scholarly research and publications to highlight critical issues pertinent to the success and uplift of Black populations across the higher education diaspora.This book will explore important issues across multiple fields--fields represented by the scholars/members of AABHE. AABHE scholars will contribute chapters based on their disciplinary expertise. The work of Earnest Boyer as articulated in the book Faculty Priorities Reconsidered: Rewarding Multiple Forms of Scholarship will be used as the conceptual foundation to ground this important work. A particular focus on the elements of Boyer's seminal work will include chapters devoted to the Scholarship of Teaching and Learning; Scholarship of Engagement; Scholarship of Discovery; and Scholarship of Integration. This scholarly book is unique in that it provides essential insight on how not only faculty, but also administrators who are invested in insuring that the priorities of the professoriate are aligned with the mission and vision of urban postsecondary institutions.